“Maranao-ness” Reconsidered: The Impact of Islam on Maranao Dance - Namiki, Kanami (Archīum Ateneo, 2018)
This study examines the production and development of dances among the Maranao, a Muslim group in the Southern Philippines. It explores the changing dance traditions and expressions of ethnic identity of Maranao dancers in the face of Islamization. It also draws attention to the role of local elites as mediators of the cultural and artistic practices and meanings between the national-center and local communities. Finally, it demonstrates how Maranao dances are sites of constant negotiation, accommodation, and resistance as local and national cultural authorities and artists struggle to define and gain control of the definition of what it means to be authentic.